2013
DOI: 10.1111/tpj.12371
|View full text |Cite
|
Sign up to set email alerts
|

AtRH57, a DEAD‐box RNA helicase, is involved in feedback inhibition of glucose‐mediated abscisic acid accumulation during seedling development and additively affects pre‐ribosomal RNA processing with high glucose

Abstract: The Arabidopsis thalianaT-DNA insertion mutant rh57-1 exhibited hypersensitivity to glucose (Glc) and abscisic acid (ABA). The other two rh57 mutants also showed Glc hypersensitivity similar to rh57-1, strongly suggesting that the Glc-hypersensitive feature of these mutants results from mutation of AtRH57. rh57-1 and rh57-3 displayed severely impaired seedling growth when grown in Glc concentrations higher than 3%. The gene, AtRH57 (At3g09720), was expressed in all Arabidopsis organs and its transcript was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 67 publications
1
48
0
Order By: Relevance
“…Extensive genetic, molecular, cellular, and biochemical analyses have uncovered the intimate links between HXK1-mediated glucose signaling and multiple hormones, including but not limited to ethylene, abscisic acid (ABA), auxin and cytokinin (Rolland et al, 2002; Leon and Sheen, 2003; Moore et al, 2003; Yanagisawa et al, 2003; Rolland et al, 2006; Huang et al, 2008; Ramon et al, 2008; Cho et al, 2010; Karve et al, 2012; Hsu et al, 2014). In maize and Arabidopsis leaf cells, Arabidopsis HXK1 but not the yeast HXK promotes the proteasome-dependent degradation of nuclear EIN3 (ETHYLENE INSENSITIVE3) and EIL1 (EIN3-LIKE1) through the C-terminus, which is stabilized by ethylene.…”
Section: Direct Glucose Sensing and Signaling Via Hxk1mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive genetic, molecular, cellular, and biochemical analyses have uncovered the intimate links between HXK1-mediated glucose signaling and multiple hormones, including but not limited to ethylene, abscisic acid (ABA), auxin and cytokinin (Rolland et al, 2002; Leon and Sheen, 2003; Moore et al, 2003; Yanagisawa et al, 2003; Rolland et al, 2006; Huang et al, 2008; Ramon et al, 2008; Cho et al, 2010; Karve et al, 2012; Hsu et al, 2014). In maize and Arabidopsis leaf cells, Arabidopsis HXK1 but not the yeast HXK promotes the proteasome-dependent degradation of nuclear EIN3 (ETHYLENE INSENSITIVE3) and EIL1 (EIN3-LIKE1) through the C-terminus, which is stabilized by ethylene.…”
Section: Direct Glucose Sensing and Signaling Via Hxk1mentioning
confidence: 99%
“…Consistently, ein3 as well as etr1, ein2 and mkk9 are hypersensitive to glucose but insensitive to ethylene (Yanagisawa et al, 2003; Yoo et al, 2008). HXK1 also modulates the glucose repression of ERF1 (ETHYLENE RESPONSE FACTOR1) in ethylene signaling, and the glucose activation of ABA2 in ABA synthesis and ABI4 / ABI5 ( ABA INSENSITIVE ) transcription factors in ABA signaling (Rolland et al, 2002; Leon and Sheen, 2003; Rolland et al, 2006; Ramon et al, 2008; Cho et al, 2010; Hsu et al, 2014). More detailed molecular mechanisms underlying sugar regulation of hormonal signaling and biosynthesis remained to be further resolved using defined HXK1 mutants, as distinct signaling and metabolic effects of sugars may be involved (Moore et al, 2003; Ohto et al, 2006; Loreti et al, 2008; Mishra et al, 2009; Mudgil et al, 2009; LeClere et al, 2010; Lin et al, 2010).…”
Section: Direct Glucose Sensing and Signaling Via Hxk1mentioning
confidence: 99%
“…Plants have comparable RNA helicases (Bush et al, 2009), but their role in plant translation has not been elucidated and they may also have other specific roles in post-transcriptional processes. For example, the nuclear-localized AteIF4AIII was shown to function in nuclear pre-mRNA/mRNA movement during hypoxia (Koroleva et al, 2009a;Koroleva et al, 2009b) and the DEAD box helicase AtRH57 appears to be involved in rRNA processing in response to glucose and abscisic acid (Hsu et al, 2013).…”
Section: Eif4 Groupmentioning
confidence: 99%
“…Sucrose density gradients were performed as described (Hsu et al 2014) because we observed inefficient release of nucleolar preribosomes using our standard procedure (Missbach et al 2013;Weis et al 2014). Total cell lysate from A. thaliana cell culture was separated on a 10%-40% (w/v) sucrose gradient by centrifugation for 18 h at 100,000g in a TST41.14 rotor.…”
Section: Sucrose Density Gradientmentioning
confidence: 99%